1996
DOI: 10.1055/s-2007-979551
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Onset of Action of Antidepressant Drugs? Survey of Results of Zurich Meta-Analyses

Abstract: The onset of action of antidepressant drugs was investigated on the basis of two independent, multicenter, double-blind studies, comparing amitriptyline (N = 120), oxaprotiline (N = 120), imipramine (N = 506) and moclobemide (N = 580) with placebo (N = 189/+191). Highly significant differences between the active drugs and placebo were found with respect to the total number of improvers and the total number of responders. In addition, significant differences between treatment modalities showed up in both the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
30
0

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(36 citation statements)
references
References 9 publications
6
30
0
Order By: Relevance
“…Clinical studies about imipramine indicate that most patients show some response within the first 1-3 weeks of therapy (Blier, 2001;Jain, 2004) and onset benefits of imipramine can be seen after 2 weeks, but its greater efficacy may take up to 4-8 weeks to observe (Stassen et al, 1996). Rogoz et al reported increased BDNF gene expression in hippocampus in normal rat brains after 14 days of imipramine administration (Rogoz and Legutko, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies about imipramine indicate that most patients show some response within the first 1-3 weeks of therapy (Blier, 2001;Jain, 2004) and onset benefits of imipramine can be seen after 2 weeks, but its greater efficacy may take up to 4-8 weeks to observe (Stassen et al, 1996). Rogoz et al reported increased BDNF gene expression in hippocampus in normal rat brains after 14 days of imipramine administration (Rogoz and Legutko, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…This general opinion on the sensitivity of the self-rating scales, especially during the early treatment period, is supported by findings of clinical trials (Müller, Müller and Volz, 1996;Stassen et al 1996). Stassen et al 1996 have found that, on the 20% reduction from the baseline score criterion of the Hamilton Anxiety Scale (HAMA), on day 6, for both active treatment groups (oxaprotiline and amitriptyline), 12.3% and 12.5% of patients respectively showed an onset of improvement, whereas on the Zung self rating scale these values were 2.3% and 5.2%, respectively. Similar findings were obtained for day 7 (HAMA: oxaprotiline 26%, amitryptiline 37.5%, Zung: oxaprotiline 4.5%, amitryptiline 20.7%).…”
Section: Introductionmentioning
confidence: 67%
“…On the basis of all 429 cases they determined the 'natural variability' of HAMD and HAMA scores (spontaneous fluctuations and error variation due to instrument and observer). Later, they found that the change of 15-25% in relation to the corresponding initial values 'over the first 3 days' (Stassen, Angst and Delini-Stula, 1996) represents a suitable threshold for a response definition of onset of improvement. Taking some other considerations into account, they proposed a 20% decrease in the initial HAMD score as the threshold that defines onset of action.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, the sum score reduction of Z20%, which is commonly used to define EI for the HAMD 17 scale (Lam, 2012;Stassen et al, 1996;Szegedi et al, 2003Szegedi et al, , 2009, is not yet validated for the HAMD subscales. Compared to the HAMD 17 , the score variability of the subscales is limited due to fewer items; therefore, a cut-off which is lower than 20% might apply, because the total score is not biased by items which are insensitive to depressive change (e.g., insight, loss of weight).…”
Section: Introductionmentioning
confidence: 99%